Authoritarian powers Russia and China compared - White, Stephen, 1945-; McAllister, Ian; Munro, Neil, 1970- (Routledge Europe-Asia Studies series, 2018)
The statistics detailing the socioeconomic growth of Russia and China are impressive. On some projections, China will be the world's largest economy by 2050, and Russia will be the sixth largest. Yet despite this impressive record of economic growth, a striking feature of both countries is the inegalitarian nature of their development - notwithstanding the (post)communist legacy. On most conventional measures, the two countries are now among the most unequal in the world, and the level of inequality has increased significantly since the 1990s. What effect does this endemic economic inequality have on political stability? From Aristotle onwards, observers have concluded that the greater the inequality within a society, the greater the likelihood of instability. This book addresses the relationship between economic inequality and political stability in Russia and China. Several chapters examine how economic performance has driven institutional reform, while others evaluate long term trends in public opinion to see how economic change has affected the public's views of politics. The conclusion is that both regimes have proved adept at adapting to rising inequality by managing the policy agenda, guiding public opinion and co-opting or repressing political opposition. 00The chapters in this book were originally published as a special issue in Europe-Asia Studies.